Development of "Marine Eco-Adventure" Educational Game Integrating Larungan Traditions to Enhance Junior High Disaster Preparedness - Fitria Nikmah, Zharifah Eka; Lutfia, Irma; Maulida, Nisrina Rahma; Herdiana, Alifia Zahra; Hidayah, Nabila Nurul; Tyas, Rizki Arumning (Berkala Ilmiah Pendidikan Fisika, 2024)
The strategy to improve student preparedness for disasters is to integrate the basic concepts of disaster in learning with local wisdom related to the sea, such as the use of “Marine Eco-Adventure” marine educational games that integrate the sidiqtraditions of defence with the context of disastrous events. The research aims to discover Marine Eco-Adventure's development, viability, and effectiveness as an educational game that can improve disaster preparedness. The research uses a qualitative approach with a one-group pre-test and post-test design. The sample used is randomly selected. The data was collected through dual selection questions (pre-test and post-test) and analyzed with the t-test. The research showed that the Marine Eco-Adventure developed deserved to be used in learning, with validation results from material and media experts in high categories. Marine Eco-Adventure is effective in improving preparedness for disaster mitigation. The findings suggest that integrating local wisdom with disaster education through interactive games like Marine Eco-Adventure can enhance students' awareness and readiness for disaster events. It highlights the potential for educational games to make learning engaging, culturally relevant, and impactful in real-world contexts. The implications of this research suggest that similar educational tools can be adapted and implemented in other regions to integrate local wisdom with disaster preparedness education, thereby fostering a deeper cultural connection and enhancing overall community resilience.